(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
The research seeks to achieve a set of objectives, the most important of which is measuring the impact of using artificial intelligence techniques in improving the disclosure process in financial statements and its reflection in sustainable development. In consistency with the importance of the research and through its problem, the researchers sought to test the research hypotheses. To achieve this, a questionnaire was designed using (Google Form) and distributed on line to the elements of the research sample that were selected using the intentional sample consisting of employees of the departments of (financial affairs, auditing and internal control). (50) answers were obtained. Through the Statistical Package for Social Sciences (SPSS) application, the results of the questionnaire were analyzed. According to the applied framework of the research, a set of findings were reached, the most important of which were: Robotic process automation technology supports the accounting disclosure process in the financial statements prepared by the Presidency of the University of Basrah, which achieves sustainable development elements. The researchers presented a set of recommendations, the most prominent of which is that the Presidency of the University of Basra issue rules and instructions under which it is committed to converting to Use of artificial intelligence techniques.